On the taxonomy of the genus Afrasura Durante, 2009, with description of a new species from Tanzania (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V. (Zootaxa, 2019)
Present paper contains description of a new species, Afrasura tanzaniae Volynkin, sp. nov. from Tanzania. The new species is related to Afrasura rivulosa (Walker, 1854). Male of Afrasura pallescens Durante, 2009 is illustrated here for the first time, with its re-description provided. Afrasura terlineata Durante, 2009 is transferred to the genus Siccia Walker, 1854: Siccia terlineata (Durante, 2009), comb. nov. Adults, male and female genitalia of all species mentioned are illustrated.